Identify the Influence of Ingredients and Cake Baking for Cupcake using Design of Experiments - Siti Nurrohkayati, Anis; ., Binyamin (International Journal of Engineering and Technology, 2019)
This experiment purpose is to determine the best recipe for cupcakes, what factors that can affect the taste of cupcake and to identify the main factors which influential significantly to the best recipe of cupcake. The parameter of the best cupcake is judged on taste, moistness, and smoothness. Taste and smoothness is rated by expert, then the moistness is measure by gram. Taguchi’s experimental design method, orthogonal arrays of Taguchi, overall evaluation criteria, design of experiments, ANOVA analysis, and S/N-ratio analysis are used to evaluate the significance influence of ingredients and cake baking for cupcake. Confirmation experiments with the significantly effect of ingredients levels was carried out in order to illustrate the effectiveness of the Taguchi’s design of experiments method. The factors which have significantly influence is the combination between sugar and fluid milk with the highest contribution i.e. 58.06%. The high amount of sugar and the use of fluid milk can affect the texture of cupcake became not good or became coarse.